2022
DOI: 10.1021/acsami.2c04745
|View full text |Cite
|
Sign up to set email alerts
|

Reprogrammable Soft Swimmers for Minimally Invasive Thrombus Extraction

Abstract: Thrombosis-related diseases are the primary cause of death in the world. Despite recent advances in thrombosis treatment methods, their invasive nature remains a crucial factor, which leads to considerable deadly consequences. Soft magnetic robots are attracting widespread interest due to their fast response, remote actuation, and shape reprogrammability and can potentially avoid the side effects of conventional approaches. This paper outlines a new approach to the thrombosis treatment via reprogrammable magne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…As guided by the roadmap, both responsive particles and polymer matrices play a vital role. ,, The former is special because the magnetization states of particles, including the direction and switching fields, can be encoded in their structure, composition, and spatial distributions. The encoded magnetic properties can be translated into forces and torques in the soft matrix materials, which is similar to programming the ensemble structures, to allow their use in the development of intelligent microrobots.…”
Section: Technological Trend Of Designing and Manufacturing Responsiv...mentioning
confidence: 99%
“…As guided by the roadmap, both responsive particles and polymer matrices play a vital role. ,, The former is special because the magnetization states of particles, including the direction and switching fields, can be encoded in their structure, composition, and spatial distributions. The encoded magnetic properties can be translated into forces and torques in the soft matrix materials, which is similar to programming the ensemble structures, to allow their use in the development of intelligent microrobots.…”
Section: Technological Trend Of Designing and Manufacturing Responsiv...mentioning
confidence: 99%
“…At Daegu Gyeongbuk Institute of Science and Technology, Hwang et al [43] reported that an electromagnetically controllable micro-robot intervention system could help doctors remotely manipulate micro-diameter guidewires in real time and complete cardiovascular interventions in vascular phantoms. At ITMO University, Pozhitkova et al [44] proposed an attractive solution for thrombosis treatment via reprogrammable magnetic soft robots. At the Massachusetts Institute of Technology, Kim et al [45] proposed a teleoperated robotic neuro-interventional platform based on magnetic manipulation.…”
Section: Laboratory Robotsmentioning
confidence: 99%
“…44 These materials consist of soft matrices with embedded hard magnetic particles, and the interaction between the magnetic torque and internal mechanical force allows for the remote control of such systems. The mechanical force from such magnetic soft robots has already shown their effectiveness for model thrombosis treatment, 45,46 drug or object delivery, 47,48 and catheter guiding for surgical applications. 35,49 Herein, we demonstrate the use of magnetic soft robots for biofilm eradication in vitro.…”
Section: Introductionmentioning
confidence: 99%